Translocated to the fringe: genetic and niche variation in bighorn sheep of the Great Basin and northern Mojave deserts. Issue 9 (28th April 2015) - Malaney, Jason L.; Feldman, Chris R.; Cox, Michael; Wolff, Peregrine; Wehausen, John D.; Matocq, Marjorie D.; Austin, Jeremy
Abstract Aim Conservation biologists use various approaches to augment imperilled populations in order to supplement genetic variation and restore ecological function. However, understanding genotypic, phenotypic and ecotypic variation is critical in determining the most suitable sources to conserve historical and functional variation. Bighorn sheep (Ovis canadensis) provide a classic example of restoration biology, where management programmes have re‐established extirpated populations via translocations. Through this process, translocated individuals may now face novel environments, including new bioclimatic conditions and an opportunity to interbreed with historically isolated and distinct genetic units. Our goal was to integrate genetic and ecological analyses to assess some of the evolutionary ramifications of this important management practice. Location Western North America, but focused on the Great Basin and northern Mojave deserts. Methods We quantified genetic variation across 55 Herds of bighorn sheep using 16 microsatellite loci (N = 347) and a mitochondrial gene (N = 110). We used ordination, Bayesian clustering and phylogenetic analyses to delineate evolutionary units. We used multivariate ordination for 26 ecologically relevant variables to characterize niche‐based differences among genetic clusters and then tested whether repatriated populations occupy conditions similar to source areas. Results We document genetic differentiation among three traditional management units of bighorn sheep that now occupy the Great Basin and northern Mojave deserts, but also identify limited hybridization among these groups. Niche‐based analyses revealed that translocated populations now occur in conditions incongruent with source ranges. Main conclusions This study highlights the importance of considering both genetic variation and ecological differences when implementing translocations. Early consideration of these variables may help minimize the potential for hybridization among distinct groups and mitigate challenges of managing populations experiencing novel environments. More broadly, results from this study have implications for future restoration efforts in this iconic system, but also for similar translocation‐based conservation programmes.